Love in the time of cholera [videorecording (DVD)] - Newell, Mike, 1942-; Bratt, Benjamin, 1963-; Mezzogiorno, Giovanna, 1974-; Bardem, Javier, 1969-; García Márquez, Gabriel, 1927-2014 (New Line Home Entertainment : Distributed by Warner Home Video, 2008)
Florentino is a poetry-writing telegraph operator who lives in a Central American city. He spots the graceful Fermina while making his rounds, and finds himself in love. While Florentino's mother encourages the courtship, Fermina's father absolutely forbids it. Years pass, and the well-born Dr. Urbino treats Fermina for a case of cholera. When Urbino proposes, Fermina accepts. A distraught Florentino decides to wait. With the help of his uncle, he amasses wealth of his own. All the while, he drifts from woman to woman, never really finding what he is looking for in a woman. After five decades of waiting, he gets a second chance to win Fermina's heart.